Surface tension-driven self-folding polyhedra - Leong, Timothy G (Langmuir : the ACS journal of surfaces and colloids, 2007)
We discuss finite element simulations and experiments involving the surface tension-driven self-folding of patterned polyhedra. Two-dimensional (2D) photolithographically patterned templates folded spontaneously when solder hinges between adjacent faces were liquefied. Minimization of interfacial free energy of the molten solder with the surrounding fluidic medium caused the solder to ball up, resulting in a torque that rotated adjacent faces and drove folding. The simulations indicate that the folding process can be precisely controlled, has fault tolerance, and can be used to fold polyhedra composed of a variety of materials, ranging in size from the millimeter scale down to the nanometer scale. Experimentally, we have folded metallic, arbitrarily patterned polyhedra ranging in size from 2 mm to 15 microm